Service quality dimensions: tourist satisfaction towards heritage tourism in A Famosa, Melaka / Norkhairunnisa Mad Sabi - Mad Sabi, Norkhairunnisa (Faculty of Business and Management, 2014)
This study focuses on “Service Quality Dimensions: Tourist Satisfaction towards Heritage Tourism in A Famosa, Melaka” and generally, the objective of this research is to find out the degree of satisfaction of the tourist towards the service quality of heritage tourism in A Famosa, Melaka. This research also developed to identify the tourist profiling, the relationship with the reliability, assurance, tangibles, empathy and responsiveness towards tourist’s satisfaction, service quality dimension that most important for tourist’s satisfaction and to identify appropriate recommendation to increase tourist’s satisfaction. The populations of this research were 6,889,134people and from that, 120 questionnaires were distributed equally at A Famosa, Dataran Pahlawan, Christ Church, Museums, Proclamation of Independence Memorial and Tourist Information Centre. Based from useful 120 questionnaires analyzed, researcher conclude that the service quality dimensions have significant relationship with tourist satisfaction but certain area can be improve in order to increase the tourist’s satisfaction towards heritage tourism in A Famosa Melaka.